2005
DOI: 10.1021/jf0479719
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor Pathways as Targets for Functional Foods

Abstract: The etiology of most chronic angiogenic diseases such as rheumatoid arthritis, atherosclerosis, diabetes complications, and cancer includes the presence of pockets of hypoxic cells growing behind aerobic cells and away from blood vessels. Hypoxic cells are the result of uncontrolled growth and insufficient vascularization and have undergone a shift from aerobic to anaerobic metabolism. Cells respond to hypoxia by stimulating the expression of hypoxia inducible factor (HIF), which is critical for survival under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 214 publications
0
18
0
Order By: Relevance
“…Due to the wide range of biological functions of HIF-1a pathway in cancer biology especially in tumor angiogenesis, HIF-1a has emerged as a potential novel molecular target for chemoprevention and therapy of cancers, including cervical cancers (53). An increasing body of evidence has indicated that inhibition of HIF-1a pathway-induced angiogenesis by synthetic small molecules or naturally occurring functional food components may provide an effective means of chemoprevention of a variety of cancers (53,54). Resveratrol, a natural antioxidant and polyphenol, has been considered a potential chemopreventive agent (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide range of biological functions of HIF-1a pathway in cancer biology especially in tumor angiogenesis, HIF-1a has emerged as a potential novel molecular target for chemoprevention and therapy of cancers, including cervical cancers (53). An increasing body of evidence has indicated that inhibition of HIF-1a pathway-induced angiogenesis by synthetic small molecules or naturally occurring functional food components may provide an effective means of chemoprevention of a variety of cancers (53,54). Resveratrol, a natural antioxidant and polyphenol, has been considered a potential chemopreventive agent (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…HIF is a transcription factor that can activate a considerable number of genes, including VEGF [1951,2246-2250]. In contrast to the constitutive expression of HIF-1α, HIF-1β protein levels are regulated in response to the cellular oxygen concentration [2251].…”
Section: Hypoxia-inducible Factor (Hif)mentioning
confidence: 99%
“…Leptin and leptin receptor (ObR) were significantly overexpressed in TNBC, and ObR expression was induced by hypoxia in TNBC cells (56). Obesity is associated with tissue hypoxia (57). Higher levels of circulating leptin promote breast cancer cell proliferation by activation of the mitogen-activated protein kinase (MAPK) and phosphoinositide 3 kinase signaling pathways (58).…”
Section: Insulin Resistance Insulin-like Growth Factor 1 (Igf-1) Andmentioning
confidence: 99%